2019
DOI: 10.1029/2019jc015287
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed CO2 Outgassing by an Enhanced Biological Pump in the Eastern Tropical Pacific

Abstract: The Eastern Tropical Pacific (ETP) is the largest oceanic source of carbon dioxide (CO 2 ) to the atmosphere. Sinking particle fluxes at a depth of 4,950 m (50 m above the seafloor) in the ETP were monitored from 2003 to 2013, during which the Pacific decadal oscillation (PDO) shifted from a positive to negative phase. We show a disproportionate increase in the efficiency of the biological pump in this region relative to the increase in primary production that occurred during La Niña years following the shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, the trend in pCO 2 should be ∼ 0 with increasing pCO 2 (atm) . This could suggest a missing component within the SA-FNN to estimate pCO 2 (sw) , such as changes in the biological export efficiency (Kim et al, 2019), which could then suppress upwelling-induced CO 2 outgassing.…”
Section: Multi-year Trends In Pco 2 and Co 2 Fluxmentioning
confidence: 99%
“…Therefore, the trend in pCO 2 should be ∼ 0 with increasing pCO 2 (atm) . This could suggest a missing component within the SA-FNN to estimate pCO 2 (sw) , such as changes in the biological export efficiency (Kim et al, 2019), which could then suppress upwelling-induced CO 2 outgassing.…”
Section: Multi-year Trends In Pco 2 and Co 2 Fluxmentioning
confidence: 99%
“…An increase in ΔpCO2 is counter intuitive for the Equatorial upwelling where ΔpCO2 would in theory decrease with increasing pCO2 (atm), assuming a constant deep water CO2 concentration. This could suggest a missing mechanism within the SA-FNN to estimate pCO2 (sw), such as changes in the biological export efficiency (Kim et al, 2019), which could suppress upwelling induced CO2…”
Section: Long Term Trends In δPco2 and Co2 Fluxmentioning
confidence: 99%
“…15 of 24 There have been studies revealing decadal changes in biogeochemical fields in the tropical Pacific resulting from the underlying physical changes due to the PDO phase shifts (Kim et al, 2019;Rodgers et al, 2008;Uz et al, 2017). For example, a modeling study showed a decrease in iron and chlorophyll levels in the upwelling region of the equatorial Pacific following the 1976/1977 PDO regime shift (Rodgers et al, 2008); Chavez et al (2003) reported that the Pacific Ocean changed from a cool "anchovy regime" to a warm "sardine regime" in the mid-1970s, then shifted back to an anchovy regime in the late 1990s.…”
Section: 1029/2020jc016515mentioning
confidence: 99%